Relationship between the Balance of Hypertrophic/Hyperplastic Adipose Tissue Expansion and the Metabolic Profile in a High Glucocorticoids Model - Zubiría, María Guillermina (2016)
Adipose tissue (AT) expansion is the result of two processes: hyperplasia and hypertrophy; and both, directly or indirectly, depend on the adipogenic potential of adipocyte precursor cells (APCs). Glucocorticoids (GCs) have a potent stimulatory effect on terminal adipogenesis; while their effects on early stages of adipogenesis are largely unknown. In the present work, we study, in a model of high GC levels, the adipogenic potential of APCs from retroperitoneal AT (RPAT) and its relationship with RPAT mass expansion. We employed a model of hyper-adiposity (30- and 60-day-old rats) due to high endogenous GC levels induced by neonatal treatment with L-monosodium glutamate (MSG).We found that the RPAT APCs from 30-day-old MSG rats showed an increased adipogenic capacity, depending on the APCs’ competency, but not in their number. Analyses of RPAT adipocyte diameter revealed an increase in cell size, regardless of the rat age, indicating the prevalence of a hypertrophic process. Moreover, functional RPAT alterations worsened in 60-day-old rats, suggesting that the hyperplastic AT expansion found in 30-day-old animals might have a protective role. We conclude that GCs chronic excess affects APCs’ adipogenic capacity, modifying their competency. This change would modulate the hyperplastic/hypertrophic balance determining healthy or unhealthy RPAT expansion and, therefore, its functionality.